Penerapan Sanksi Denda pada Pembiayaan Bai’ Bitsaman Ajil di Baitul Maal Wat Tamwil (BMT) Pahlawan Tulungagung atas Keterlambatan dalam Pembayaran Angsuran - Fatkhur Rohman Albanjari; Rokhmat Subagyo (Universitas Islam Kadiri, 2019)
This research aims to know us applying sanctions and penalty on financing ' bai bitsaman ajil at the BMT Pahlawan Tulungagung for the delay in payment of the installments. The author's methods of research conducted in this study using a qualitative approach. As for the type of research is descriptive, meaning that the data collected is in the form of words, images, and not the numbers. The results showed that the application of fines in BMT Pahlawan Tulungagung is in compliance with the Shariah Board Fatwa of the national assemblies of scholars of Indonesia No. 17/DSN-MUI/IX/2000. In its application of fines charged to borrowers who can afford but procrastinate the payout as well as clients who do not have good faith to settle the payment.